2015
DOI: 10.1007/s11469-015-9580-z
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions as a Moderator of the Associations Between Self-Control and Social Support Among Adolescents with Risk Behaviors

Abstract: The present study investigated the moderating role of positive emotions on the associations between self-control and social support with gambling and water-pipe smoking. One hundred fifty-five adolescents aged 12-19 (M=16.19) were contacted in 2011 at five centers for at-risk youth in Israel. Self-report findings indicated that positive emotions moderated the associations between peer social support and gambling and between self-control and water-pipe smoking. Among adolescents with higher rates of positive em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A growing number of studies have reported an Waterpipe use in adolescents in Northern Sweden: Association with mental well-being and risk and health behaviours association between waterpipe use and cigarette smoking [1,13,14]. A few studies have also found that waterpipe use in adolescents is related to other risk behaviours, including use of e-cigarettes [15], snus, alcohol and narcotics [16], as well as gambling [17]. Although waterpipe smoking has been associated with risky health behaviours and can also lead to nicotine dependence [18,19], no prior studies have determined whether such behaviour is also associated with adolescents' mental well-being.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have reported an Waterpipe use in adolescents in Northern Sweden: Association with mental well-being and risk and health behaviours association between waterpipe use and cigarette smoking [1,13,14]. A few studies have also found that waterpipe use in adolescents is related to other risk behaviours, including use of e-cigarettes [15], snus, alcohol and narcotics [16], as well as gambling [17]. Although waterpipe smoking has been associated with risky health behaviours and can also lead to nicotine dependence [18,19], no prior studies have determined whether such behaviour is also associated with adolescents' mental well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This study explains that users with high self-control levels would usually have more self-confidence in their ability to overcome the requirements for new ICT's implementation (Gavriel-Fried and Ronen 2016). It means that ICT users could reduce the negative impact of technostress due to their self-efficacy.…”
Section: Technostress Self-control Performance Feedback and Ict's User Outcomesmentioning
confidence: 94%
“…Beyond examining individual developmental pathways of vulnerable children and youth and their family resources as discussed previously, these studies have explored the health-enhancing capacities of the community and, especially, of the school system. Thus, protective factors at the community level may include peer relationships, non-family-member relationships, non-family-member social support, and religion, among others (Keyes, 2006;Gavriel-Fried & Ronen, 2016;Orkibi, Hamama, Gabriel-Fried, & Ronen, 2018).…”
Section: The Role Of Schools In Developing Resiliencementioning
confidence: 99%